Functional oils affect blood and bacteriological parameters in sheep - da Silva, Lúcio F. M.; de Oliveira, Maria C.; dos Santos, Nayara F.; Paludo, Alexsandra; Gomes, Yeury de S.; do Amaral, Anaiza S. Z. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Feeding ionophores to sheep is intended for improving feed efficiency. Functional oils (FO) are an alternative to the use of ionophores. Objective: To evaluate the effect of feeding FO to sheep on blood parameters and fecal bacteria. Methods: Five sheep were used in a Latin square design with five treatments: 190, 285, 380, 570, and 675 g/t FO in the diet. White cell count and levels of blood glucose, total protein, urea nitrogen, and fecal bacteria presence in feces were determined. Results: The FO levels did not affect serum parameters. Salmonella spp was found only in feces of sheep fed 190 mg/t FO. Conclusion: Functional oils can be added to sheep diets to reduce the presence of Salmonella spp in the feces.